Этнография народов Томской области: учебное пособие - Бардина П. Е.; Гончарова Т. А.; Грошева Г. В.; Кошелева Е. Ю. Елена Юрьевна; Локтионова А. А.; Лукина Н. В.; Максимова И. Е.; Парнюк Л. В.; Тучкова Н. А. (Томск, Изд-во ТГПУ, 2009)
В фонде НТБ ТПУ отсутствует